2015
DOI: 10.1021/acs.jced.5b00080
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Cationic Dye Adsorption of Novel Fe3O4 Supermagnetic/Thiacalix[4]arene Tetrasulfonate Self-Doped/Polyaniline Nanocomposite: Kinetics, Isotherms, and Thermodynamic Study

Abstract: In this study, a novel magnetically separable nanoadsorbent, namely, Fe 3 O 4 @PAmABAmPD-TCAS consisting of a magnetite core and conductive terpolymer of aniline/m-aminobenzoicacid/m-phenilendiamine shell which was self-doped by protonic acid of thiacalixarene tetrasulfonate pendent groups has been synthesized in a three step procedure. Adsorption features of the magnetic nanoadsorbent were evaluated by using methylene blue (MB) and malachite green (MG) as adsorbates. The isotherms, kinetics, and thermodynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Free hydroxyl ions (OH − ) remained in the solution, thus there may be an interaction of MB dye molecules with negative OH − occurring, forming MB−OH complexation thus blocking the adsorption process on the surface of wsONC. So, it was found that at only pH 7−8, 62 the adsorption capacity of wsONC was at a maximum, where almost no interfering ions were present in the system and surface was negatively charged. Additionally, the effect of ionic strength on the adsorption capacity of wsONC was also studied by taking different concentrations of NaCl salt solution (Figure S2, Supporting Information).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Free hydroxyl ions (OH − ) remained in the solution, thus there may be an interaction of MB dye molecules with negative OH − occurring, forming MB−OH complexation thus blocking the adsorption process on the surface of wsONC. So, it was found that at only pH 7−8, 62 the adsorption capacity of wsONC was at a maximum, where almost no interfering ions were present in the system and surface was negatively charged. Additionally, the effect of ionic strength on the adsorption capacity of wsONC was also studied by taking different concentrations of NaCl salt solution (Figure S2, Supporting Information).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The Freundlich [32] isotherm can be applicable for modelling the adsorption of dye on heterogeneous surfaces and the linearised form of isotherm is expressed as logq e D logK f C ð1=nÞ Ã logC e (6) where K F (mg/g) is Freundlich constant representing the adsorption capacity at unit equilibrium concentration that is defined as the adsorption or distribution coefficient and 1/n is related to the adsorption intensity. The value of Freundlich constant 'n' is greater than 1.0, as shown in Figure 10(d), indicating that RhB favourably adsorbed on L-Ser capped Fe 3 O 4 NPs.…”
Section: Adsorption Isothermmentioning
confidence: 99%
“…Instead, adsorption is promising technology for an effective treatment of polluted water due to it is low-cost, simply designed, easy to handle, and provides sludge-free output [4,5]. Activated carbon has been long known for an effective colour removal adsorbent, but its expensive operation cost unable to address for a wide range of consumers [6]. Hence developing of alternative adsorbents of less cost, ease of operation and simplistic design has been the focus of recent research.…”
Section: Introductionmentioning
confidence: 99%
“…The slope of the plot of ln qe versus ε² gives K (mol 2 (kJ ) and the intercept yields the adsorption capacity; QS (mg g -1 ). The mean free energy of adsorption (E), for transfer of one mole of the target from infinity in solution to the surface of the solid was calculated from the K value using the following relation (Lakouraj et al, 2015):…”
Section: Numerical Optimization Of Decolorization Processmentioning
confidence: 99%